KEGIATAN PENANAMAN MANGROVE SEBAGAI SALAH SATU UPAYA PELESTARIAN EKOSISTEM PESISIR DI DESA KERSIK, KABUPATEN KUTAI KARTANEGARA - Marlinda, Nanda; Natania Ibrahim, Sabina; Sanjaya, Arwin; Arie Hetami, Adietya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Kersik Village is located in Marangkayu District, Kutai Kartanegara Regency, East Kalimantan. Kersik village is called a tourist village because it has a famous tourist destination, namely Blue Kersik Beach. Biru Kersik Beach has the opportunity to utilize the mangrove ecosystem which has not been utilized productively by the surrounding community. Most of the people of Kersik Village do not understand the role provided by the mangrove ecosystem. Therefore, an empowerment effort is needed to increase community understanding by carrying out mangrove planting activities. The method used in this activity includes a survey stage, where this step aims to confirm the location of mangrove planting by identifying which areas need the most planting. As additional information, an interview process was also carried out at one of the organizations in Kersik Village, namely Sahabat Mangrove. The results to be achieved from this community service are (1) to instill an understanding in the younger generation as agents of future change regarding the role of mangroves so as to create a commitment to protecting and preserving the environment, especially the mangrove ecosystem as a potential owned by the region, namely the coastal tourist attraction of Biru Kersik Beach. , (2) the output target to be achieved from this service activity is the addition of mangrove vegetation as an effort to preserve the coastal ecosystem in Kersik Village, Kutai Kartanegara Regency. It is hoped that the community around the coastal tourism area of ??Biru Kersik Beach can be further programmed to carry out outreach regarding the ecological function of mangrove forests. Evaluation is carried out through regular monitoring of mangrove growth, such as (1) Measuring how many mangrove seedlings have successfully grown and survived after a certain period, (2) Observing the growth in height and diameter of mangrove stems over several months and (3) Checking the health condition of the mangrove, including leaves, stems, and roots to detect disease or other problems.